Is nephrostomy tube a rule following all Percutaneous Nephrolithotomy (PCNL)? A prospective randomized study - Pawan Raj Chalise (Society of Surgeons of Nepal, 2017)
Introduction: Exit strategy at the end of percutaneous nephrolithotomy (PCNL) differs from center to center and patient to patient. Standard PCNL has been practiced so far with minor postoperative morbidities. Tubeless PCNL, which obviates most of the nephrostomy related morbidities, has been challenged for its safety. So this study was conducted to compare the safety and morbidity of tubeless PCNL with standard PCNL.